Feto-mone Gender Paradigm in the Culture and Architecture of the Dawan Tribe Settlement in Kaenbaun Village - Yohanes Djarot Purbadi; Reginaldo Christophori Lake; Bonifasius Sumardiyanto; Yohanes Taus (Wacana Seni Journal of Arts Discourse, 2021)
This article aimed to show the existence of gender concepts in the culture and settlement of the Dawan tribe in Kaenbaun Village, as indicated with its strong presence in the everyday life of the community, including the formal and ritual aspects. The concept exists in the inner world and mindset of every villager and has also become the guiding element of their world view, behaviour, place arrangement, and living space structures. This study was, there, conducted using participatory observation based on the Husserlian phenomenology paradigm supported by the inductive-empirical and qualitative descriptive methods to discover and understand the gender concept as well as its application and background in the selected tribe. The results showed the feto-mone gender concept has become a paradigm of the thought expressed broadly and consistently through words, behaviour, as well as place and spatial arrangements among the villagers. Its function and meaning were further clarified in relation to the life and settlement architecture of the people. The core principle observed to be behind the concept is the separation and integration of life elements in an intense and permanent mutualism symbiotic relationship. Therefore, it was necessary to research the concept, function, and meaning of gender in ethnic cultures throughout Indonesia in order to form a collection of knowledge on gender and spatial planning which is useful to the understanding of ethnic settlements’ uniqueness based on local or ethnic perspectives and their preservation.